2018
DOI: 10.3390/molecules23112992
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Analytical Microwave-Assisted Extraction Methods for Bioactive Compounds from Myrtle (Myrtus communis L.)

Abstract: The phenolic compounds and anthocyanins present in myrtle berries are responsible for its beneficial health properties. In the present study, a new, microwave-assisted extraction for the analysis of both phenolic compounds and anthocyanins from myrtle pulp has been developed. Different extraction variables, including methanol composition, pH, temperature, and sample–solvent ratio were optimized by applying a Box–Behnken design and response surface methodology. Methanol composition and pH were the most influent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Other good sources of anthocyanins include purple corn, cherries, plums, pomegranate, eggplant, wine, grapes, and red/purple vegetables such as black carrots, red cabbage and purple cauliflower which may contain from a few milligrams up to 200–300 mg/100 g of product [ 72 , 73 ]. More recently, anthocyanins have been identified in numerous berries whose production and consumption is steadily increasing, such as maqui [ 74 , 75 ], myrtle [ 76 , 77 ], and açai [ 78 , 79 , 80 ].…”
Section: Anthocyanins In Foodmentioning
confidence: 99%
“…Other good sources of anthocyanins include purple corn, cherries, plums, pomegranate, eggplant, wine, grapes, and red/purple vegetables such as black carrots, red cabbage and purple cauliflower which may contain from a few milligrams up to 200–300 mg/100 g of product [ 72 , 73 ]. More recently, anthocyanins have been identified in numerous berries whose production and consumption is steadily increasing, such as maqui [ 74 , 75 ], myrtle [ 76 , 77 ], and açai [ 78 , 79 , 80 ].…”
Section: Anthocyanins In Foodmentioning
confidence: 99%
“…[42] Furthermore, a substantial similarity has been recorded with the anthocyanins profile of Spanish myrtle, even though in this case a different extraction methodology has been applied. [43] Regarding the leaves of Sicilian myrtle, their extracts are characterized by the predominance of flavonols components, in particular, myricetin derivatives (as rhamnoside, glucoside and rutinoside), which largely are the main components, followed, at lower extent, by quercetin derivatives ( Table 5). Also in this case, the profile is rather similar to the analogous extracts from Sardinian myrtle, even though from the latter much more components have been identified.…”
Section: Myrtle Berries and Leaves Extracts Compositionmentioning
confidence: 99%
“…Several studies carried out in human beings and cell culture models have demonstrated the antioxidant and anti-inflammatory activities of açai pulp and açai juice [6]. These properties are mainly associated to the phenolic compounds present in this fruit [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Total phenolic compounds (TPCs) are usually related to the prevention of degenerative diseases among others, being also responsible for the antioxidant and anticancer properties of the berry [19][20][21]. Among others, syringic acid, protocatechuic acid, vanillic acid, p-coumaric, or caffeic are some of the most relevant phenolic compounds present in açai [22,23].…”
Section: Introductionmentioning
confidence: 99%